Interim Report on Causes of the Deepwater Horizon Oil Rig Blowout and Ways to Prevent Such Events - National Academy of Engineering; National Research Council (The National Academies Press, 2010)
The National Academy of Engineering and the National Research Council have released the interim report of the Committee on the Analysis of Causes of the Deepwater Horizon Explosion, Fire, and Oil Spill to Identify Measures to Prevent Similar Accidents in the Future. The interim report includes the committee's preliminary findings and observations on various actions and decisions including well design, cementing operations, well monitoring, and well control actions. The interim report also considers management, oversight, and regulation of offshore operations.
Keywords: Engineering and Technology; Environment and Environmental Studies

Persistent Forecasting of Disruptive Technologies - National Research Council (The National Academies Press, 2010)
Technological innovations are key causal agents of surprise and disruption. In the recent past, the United States military has encountered unexpected challenges in the battlefield due in part to the adversary's incorporation of technologies not traditionally associated with weaponry. Recognizing the need to broaden the scope of current technology forecasting efforts, the Office of the Director, Defense Research and Engineering (DDR&E) and the Defense Intelligence Agency (DIA) tasked the Committee for Forecasting Future Disruptive Technologies with providing guidance and insight on how to build a persistent forecasting system to predict, analyze, and reduce the impact of the most dramatically disruptive technologies. The first of two reports, this volume analyzes existing forecasting methods and processes. It then outlines the necessary characteristics of a comprehensive forecasting system that integrates data from diverse sources to identify potentially game-changing technological innovations and facilitates informed decision making by policymakers. The committee's goal was to help the reader understand current forecasting methodologies, the nature of disruptive technologies and the characteristics of a persistent forecasting system for disruptive technology. Persistent Forecasting of Disruptive Technologies is a useful text for the Department of Defense, Homeland Security, the Intelligence community and other defense agencies across the nation.
Keywords: Engineering and Technology

Persistent Forecasting of Disruptive Technologies—Report 2 - National Research Council (The National Academies Press, 2010)
The term "disruptive technology" describes a technology that results in a sudden change affecting already established technologies or markets. Disruptive technologies cause one or more discontinuities in the normal evolutionary life cycle of technology. This may lead to an unexpected destabilization of an older technology order and an opportunity for new competitors to displace incumbents. Frequently cited examples include digital photography and desktop publishing.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2009 Symposium (The National Academies Press, 2010)
In 1995, the National Academy of Engineering initiated the Frontiers of Engineering Program, which brings together about 100 young engineering leaders at annual symposia to learn about cutting-edge research and technical work in a variety of engineering fields. The 2009 U.S. Frontiers of Engineering Symposium was held at The National Academies' Arnold O. and Mabel Beckman Center on September 10-12. Speakers were asked to prepare extended summaries of their presentations, which are reprinted in this volume. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.
Keywords: Health and Medicine; Engineering and Technology

Spectrum Management for Science in the 21st Century - National Research Council (The National Academies Press, 2010)
Radio observations of the cosmos are gathered by geoscientists using complex earth-orbiting satellites and ground-based equipment, and by radio astronomers using large ground-based radio telescopes. Signals from natural radio emissions are extremely weak, and the equipment used to measure them is becoming ever-more sophisticated and sensitive.
Keywords: Computers and Information Technology; Engineering and Technology

Technology for a Quieter America - National Academy of Engineering (The National Academies Press, 2010)
Exposure to noise at home, at work, while traveling, and during leisure activities is a fact of life for all Americans. At times noise can be loud enough to damage hearing, and at lower levels it can disrupt normal living, affect sleep patterns, affect our ability to concentrate at work, interfere with outdoor recreational activities, and, in some cases, interfere with communications and even cause accidents. Clearly, exposure to excessive noise can affect our quality of life.
Keywords: Engineering and Technology; Environment and Environmental Studies

Seeing Photons: Progress and Limits of Visible and Infrared Sensor Arrays - National Research Council (The National Academies Press, 2010)
The Department of Defense recently highlighted intelligence, surveillance, and reconnaissance (ISR) capabilities as a top priority for U.S. warfighters. Contributions provided by ISR assets in the operational theaters in Iraq and Afghanistan have been widely documented in press reporting. While the United States continues to increase investments in ISR capabilities, other nations not friendly to the United States will continue to seek countermeasures to U.S. capabilities.
Keywords: Conflict and Security Issues; Engineering and Technology

Standards for K-12 Engineering Education? - National Research Council (The National Academies Press, 2010)
The goal of this study was to assess the value and feasibility of developing and implementing content standards for engineering education at the K-12 level. Content standards have been developed for three disciplines in STEM education--science, technology, and mathematic--but not for engineering. To date, a small but growing number of K-12 students are being exposed to engineering-related materials, and limited but intriguing evidence suggests that engineering education can stimulate interest and improve learning in mathematics and science as well as improve understanding of engineering and technology. Given this background, a reasonable question is whether standards would improve the quality and increase the amount of teaching and learning of engineering in K-12 education.
Keywords: Engineering and Technology; Education

Engineering, Social Justice, and Sustainable Community Development: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2010)
Engineering, Social Justice, and Sustainable Community Development is the first in a series of biennial workshops on the theme of engineering ethics and engineering leadership. This workshop addresses conflicting positive goals for engineering projects in impoverished areas and areas in crisis. These conflicts arise domestically as well as in international arenas. The goals of project sponsors and participants, which are often implicit, include protecting human welfare, ensuring social justice, and striving for environmental sustainability alongside the more often explicit goal of economic development or progress. The workshop, summarized in this volume, discussed how to achieve the following:
Keywords: Engineering and Technology; Environment and Environmental Studies

Biometric Recognition: Challenges and Opportunities - National Research Council (The National Academies Press, 2010)
Biometric recognition--the automated recognition of individuals based on their behavioral and biological characteristic--is promoted as a way to help identify terrorists, provide better control of access to physical facilities and financial accounts, and increase the efficiency of access to services and their utilization. Biometric recognition has been applied to identification of criminals, patient tracking in medical informatics, and the personalization of social services, among other things. In spite of substantial effort, however, there remain unresolved questions about the effectiveness and management of systems for biometric recognition, as well as the appropriateness and societal impact of their use. Moreover, the general public has been exposed to biometrics largely as high-technology gadgets in spy thrillers or as fear-instilling instruments of state or corporate surveillance in speculative fiction.
Keywords: Computers and Information Technology; Engineering and Technology; Conflict and Security Issues

S&T Strategies of Six Countries: Implications for the United States - National Research Council (The National Academies Press, 2010)
An increase in global access to goods and knowledge is transforming world-class science and technology (S&T) by bringing it within the capability of an unprecedented number of global parties who must compete for resources, markets, and talent. In particular, globalization has facilitated the success of formal S&T plans in many developing countries, where traditional limitations can now be overcome through the accumulation and global trade of a wide variety of goods, skills, and knowledge. As a result, centers for technological research and development (R&D) are now globally dispersed, setting the stage for greater uncertainty in the political, economic, and security arenas.
Keywords: Policy for Science and Technology; Engineering and Technology; Industry and Labor

Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2010)
In the face of so many daunting near-term challenges, U.S. government and industry are letting the crucial strategic issues of U.S. competitiveness slip below the surface. Five years ago, the National Academies prepared Rising Above the Gathering Storm, a book that cautioned: "Without a renewed effort to bolster the foundations of our competitiveness, we can expect to lose our privileged position." Since that time we find ourselves in a country where much has changed--and a great deal has not changed. So where does America stand relative to its position of five years ago when the Gathering Storm book was prepared? The unanimous view of the authors is that our nation's outlook has worsened. The present volume, Rising Above the Gathering Storm, Revisited, explores the tipping point America now faces. Addressing America's competitiveness challenge will require many years if not decades; however, the requisite federal funding of much of that effort is about to terminate. Rising Above the Gathering Storm, Revisited provides a snapshot of the work of the government and the private sector in the past five years, analyzing how the original recommendations have or have not been acted upon, what consequences this may have on future competitiveness, and priorities going forward. In addition, readers will find a series of thought- and discussion-provoking factoids--many of them alarming--about the state of science and innovation in America. Rising Above the Gathering Storm, Revisited is a wake-up call. To reverse the foreboding outlook will require a sustained commitment by both individual citizens and government officials--at all levels. This book, together with the original Gathering Storm volume, provides the roadmap to meet that goal. While this book is essential for policy makers, anyone concerned with the future of innovation, competitiveness, and the standard of living in the United States will find this book an ideal tool for engaging their government representatives, peers, and community about this momentous issue.
Keywords: Policy for Science and Technology; Education; Engineering and Technology; Industry and Labor